The Effect of Giving Aloe Vera Growth Regulators to Entres on the Success of Grafting Honey Mango Seedlings (Mangifera Indica) - Umar Husein Abdullah; Ayu Maharani; Said Mulya Ihsan; Yusran Akbar; Halim Akbar (JERAMI : Indonesian Journal of Crop Science, 2024)
This study aims to influence the administration of Aloe vera Plant Growth Regulators (PGR) on scions on the success of grafting of Honey Mango seedlings with concentrations of 2, 4, and 6 grams. The parameters observed were: Plant height was measured using a ruler by measuring from the ground surface to the tip of the highest stem. Stem diameter was measured at a height of 1 cm above the ground surface using a digital caliper. The number of leaves counted were leaves that were fully open. The calculation of the number of leaves was carried out since two weeks after planting. Stem diameter measurements were carried out since two weeks after planting and then measured once a week for seven weeks. To see the factors that affect the Treatment (M0, M1, M2, and M3) on Plant Height, Stem Diameter and Number of Leaves, multiple linear regression was used. In addition to the PGR factor, factors such as weather, nutrients and soil type greatly affect plant growth (Saputro et al., 2017; Sipayung et al., 2024). It can be seen that the M3 treatment (6 grams of PGR) had a greater effect (50.7%) compared to the M0, M1, and M2 treatments. This indicates that the more plant growth regulators given to the plants, the greater the R square value. This is in accordance with the research of Prabawa et al., (2020) which stated that soaking natural plant growth regulators had a significant effect on the viability and vigor of expired pagoda mustard seeds, and the treatment of coconut water with a concentration of 50% (Z2) gave the best effect.